Effect of cation dopant radius on the hydrothermal stability of tetragonal zirconia: Grain boundary segregation and oxygen vacancy annihilation. (March 2016) - Zhang, Fei; Batuk, Maria; Hadermann, Joke; Manfredi, Gabriele; Mariën, An; Vanmeensel, Kim; Inokoshi, Masanao; Van Meerbeek, Bart; Naert, Ignace; Vleugels, Jef
Abstract: The hydrothermal aging stability of 3Y-TZP-xM2 O3 (M = La, Nd, Sc) was investigated as a function of 0.02–5 mol% M2 O3 dopant content and correlated to the overall phase content, t -ZrO2 lattice parameters, grain size distribution, grain boundary chemistry and ionic conductivity. The increased aging stability with increasing Sc2 O3 content and the optimum content of 0.4–0.6 mol% Nd2 O3 or 0.2–0.4 mol% La2 O3, resulting in the highest aging resistance, could be directly related to the constituent phases and the lattice parameters of the remaining tetragonal zirconia. At low M2 O3 dopant contents ≤0.4 mol%, the different aging behavior of tetragonal zirconia was attributed to the defect structure of the zirconia grain boundary which was influenced by the dopant cation radius. It was observed that the grain boundary ionic resistivity and the aging resistance followed the same trend: La 3+ > Nd 3+ > Al 3+ > Sc 3+, proving that hydrothermal aging is driven by the diffusion of water-derived mobile species through the oxygen vacancies. Accordingly, we elucidated the underlying mechanism by which a larger trivalent cation segregating at the zirconia grain boundary resulted in a higher aging resistance. Graphical abstract: